Karakteristik Hujan Jam-Jaman Berdasarkan Data Satelit TRMM JAXA Kabupaten Pelalawan - Khotimah, Gina Khusnul; Handayani, Yohanna Lilis; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Rainfall characteristic is a feature or kind of rainfall every hour, in the rainfall duration or rainfall distribution. Rainfall duration is the time that counts as rainfall begin to descend until its stops. Rainfall distribution is expressed in a time function that describes the variation in depth of rainfall during expressed in the graph. Rainfall characteristic analysis in this research in Pelalawan Regency based on TRMM JAXA data. The results of this research its rainfall duration higher the average rainfall is also higher. The more of events then average rainfall is getting smaller. One hour duration the rainfall distribution similar uniform distribution, two hour duration the rainfall distribution similar Modified Mononobe distribution, three to nine hour and eleven to thirteen hour duration the rainfall distribution similar Alternating Block Method, and ten hour, fourteen to eighty one hour duration similar irregular distribution.Keywords: Rainfall Characteristic, Rainfall Duration , Rainfall Distribution.